Unusual metastases of breast cancer: a single-center retrospective study - Özdemir Akdur, Pınar; Çiledağ, Nazan (The European Research Journal, 2023)
Objectives: While clinical and radiological awareness of the usual, frequent metastatic sites of breast cancer is high, unexpected 'atypical' localisations may be more easily overlooked in the cancer management process. The aim of this article is to contribute to this awareness in order to facilitate and improve the diagnosis and follow-up of breast cancer. Methods: In this study, we retrospectively evaluated breast cancer patients who were diagnosed and followed up between 2017 and 2022 in our hospital, which is an important oncology center. Results: Of the 852 patients included in this study, 79 had an unusual metastasis localization. The most common unusual metastasis sites were mediastinal lymph nodes and brain. These sites were followed by atypical bone involvement, mesenteric lymph nodes, cervical lymph nodes, hilar lymph nodes and surrenal metastases. The most rare metastases were more common in the uterus and ovary, followed by pancreas, parotid gland, spleen, colon, pericardium-atrium, orbital soft tissues and lacrimal gland. . The unusual site of metastasis was mediastinal lymph nodes in 17.7% (n = 14), brain in 17.7% (n = 14), atypical bone sites in 12.6% (n = 10), mesenteric lymph nodes in 11.3% (n = 9), cervical lymph nodes in 11.3% (n = 9), hilar lymph nodes in 5% (n = 4) and surrenal in 6.3% (n = 5). Conclusions: Sharing knowledge and experience about unusual metastases of breast cancer will contribute to the diagnosis and treatment of metastatic diseases by increasing the awareness of this issue. For this, multicentre studies should be conducted to combine these experiences.